Different Innate Immune Responses in BALB/c and C57BL/6 Strains following Corneal Transplantation - Bleul, Tim; Zhuang, Xinyu; Hildebrand, Antonia; Lange, Clemens; Böhringer, Daniel; Schlunck, Günther; Reinhard, Thomas; Lapp, Thabo (Journal of innate immunity, 2021)
Purpose: To investigate immunological differences and the role of CD38+/F4/80 + M1 macrophages in C57BL/6J- and BALB/c-recipient mouse corneal transplantation models. Methods: Allogeneic transplantation was performed crosswise in BALB/c mice and C57BL/6J mice; syngeneic transplantation was performed in both strains. Anterior chamber depth (ACD) was measured before and central corneal thickness (CCT) was measured both before and after transplantation. In vivo graft rejection was monitored using anterior eye segment optical coherence tomography (ASOCT) evaluating the CCT and grading of corneal oedema using a well-established clinical score (CS). Histology of corneal grafts was performed 18 or 21 days after surgery. Immunohistochemistry with anti-F4/80 antibody and anti-CD38 antibody was used for detecting M1 macrophages within the grafts. Results: High CS and CCT values after allogeneic transplantation persisted in both BALB/c (n = 18) and C57BL/6J recipients (n = 20). After syngeneic transplantation, CS and CCT values increased in both models in the early phase after surgery due to the surgical trauma. Surprisingly, in the syngeneic C57BL/6J model, high CCT values persisted. Furthermore, anterior synechiae developed in C57BL/6 recipients after both syngeneic and allogeneic transplantation, whereas BALB/c recipients showed almost no synechiae – even though C57/BL6J animals tended to have a deeper anterior chamber (281 ± 11 pixels [mean ± SD]) compared with BALB/c animals of the same age (270 ± 9 pixels [mean ± SD]). Immunohistochemistry revealed numerous CD38+/F4/80 + M1 macrophages in grafts of C57BL/6J recipients following both syngeneic and allogeneic transplantation. However, in BALB/c-recipient mice only sparse M1 macrophages were detectable (CD38 + M1 macrophages relative to all F4/80 + cells: 75 vs. 17% [after allogeneic transplantation] and 66 vs. 17% [after syngeneic transplantation]; p < 0.05). Conclusions: Allogeneic corneal transplants are rejected in BALB/c as well as C57BL/6J mice, but tissue alterations with anterior synechiae are more pronounced in C57BL/6J recipients. Following syngeneic transplantation, C57BL/6J-recipient animals show a persistent graft swelling with increased numbers of CD38+/F4/80 + M1 macrophages in grafted tissue, in contrast to the common model using BALB/c-recipient mice. Our data strongly suggest that strain-dependent differences convey different innate immune responses in BALB/c and C57BL/6J strains. Accordingly, in murine keratoplasty experiments, the mouse line of both donor and recipient animals must be carefully considered. C57BL/6J-recipient mice might be particularly suited to study corneal graft rejection in a clinical setting considered “high risk.”